2023
DOI: 10.1080/21645698.2023.2239539
|View full text |Cite
|
Sign up to set email alerts
|

Providing appropriate information to consumers boosts the acceptability of genome-edited foods in Japan

Chie Taguchi,
Norihito Shibata,
Keisuke Soga
et al.

Abstract: The Japanese Health Ministry recently granted permission for the market distribution of genome-edited (GE) foods, yet there remains a lack of full understanding among consumers regarding this technology. In this study, we conducted a survey to assess the acceptability of GE foods among Japanese consumers and examined the impact of providing information about GE foods on their acceptability. We conducted a web-based survey among 3,408 consumers aged 20–69 years, focusing on three aspects: (1) the commercial ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recently, a study was conducted to determine the acceptability of gene-edited foods among Japanese consumers. 461 The results of this study emphasise the importance of product transparency upon public acceptance of geneedited food for consumption. Upon viewing an informative video on gene-edited food, acceptance of these foods being commercially available was found to be increased.…”
Section: Public and Regulatory Approval Of Gene Editing In Aquaculturementioning
confidence: 78%
“…Recently, a study was conducted to determine the acceptability of gene-edited foods among Japanese consumers. 461 The results of this study emphasise the importance of product transparency upon public acceptance of geneedited food for consumption. Upon viewing an informative video on gene-edited food, acceptance of these foods being commercially available was found to be increased.…”
Section: Public and Regulatory Approval Of Gene Editing In Aquaculturementioning
confidence: 78%
“…This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. of edible red seabream with increased yield (Kato, 2023), one highgrowth pufferfish ("Japan Embraces CRISPR-Edited Fish," 2022), and one PH1V69 CRISPR-Cas9 waxy corn (Taguchi et al, 2023).…”
Section: Genetic Modification-a Beacon Of Hopementioning
confidence: 99%
“… 44 On the contrary, positive framing of the rigorous risk assessment of GM crops and their importance to global food security 45 can improve the acceptability of GM and genome edited (GE) crops. 46 If GM crops are framed as sustainable by the media, it should be expected that this is also the way consumers would perceive the technology ( Fig. 2 ).…”
Section: Framing and Misrepresentation Of Gm Cropsmentioning
confidence: 99%
“…The study by Taguchi and coworkers on acceptance of GE foods in Japan found that, when consumers are provided with appropriate information, their acceptance of GE foods increases. 46 Further, there is an increase in acceptance, particularly when the information helps consumers understand why GE foods are important and how they are tested to ensure their safety. 46 This implies that a similar approach could be used for GM foods.…”
Section: Potential Routes Towards Greater Acceptance Of Gm Cropsmentioning
confidence: 99%
See 1 more Smart Citation